Reduced oxidative stress suppresses neurotoxicity in the Drosophila model of TAF15-associated proteinopathies. - Han, Y.J.; Kim, K. (Molecular brain, 2022)
TATA-binding protein associated factor 15 (TAF15) is involved in the pathology of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Although TAF15 accumulates as cytoplasmic aggregates in neurons and the clearance of aggregates may be a therapeutic strategy for ALS, the underlying mechanisms of TAF15 in ALS remain poorly understood. Recently, we found that glutathione transferase omega 2 (GstO2) expression level is significantly reduced in the brain tissue of TAF15-expressing flies. In this study, we demonstrated that GstO2 overexpression in TAF15-induced flies rescues the locomotive activity and neuromuscular junctional defects. Furthermore, TAF15 levels in both cytoplasm and nuclear fractions significantly decreased in the heads of GstO2 co-expressing flies. GstO2-co-overexpression in neurons caused a marked decrease in intracellular reactive oxygen species generation in TAF15-induced flies. Our findings demonstrated that GstO2 was a pathogenic regulator of TAF15-associated proteinopathies. They help expand our understanding of TAF15-associated ALS pathogenesis.